Multi-axis destabilisation device influences plantar pressure distribution in adults with chronic ankle instability. Issue 4 (21st April 2022) - Knuckles, Allison M.; Torp, Danielle M.; Hubbard-Turner, Tricia; Donovan, Luke; Thomas, Abbey C.
ABSTRACT: Patients with chronic ankle instability (CAI) walk with increased lateral plantar pressure, precipitating future injuries. Gait retraining to medially shift plantar pressure may prevent recurrent injury. We assessed if a multi-axis destabilisation device changed plantar pressure and muscle activity in patients with CAI during walking. Twelve adults with CAI (age: 23.6 ± 5.0 years; body mass index: 26.7 ± 4.5 kg/m2) participated. Insole plantar pressure and electro-myography were collected synchronously during treadmill walking. The destabilisation device had a half-sphere under both the rearfoot and forefoot. Two 30s walking trials were recorded at baseline, first without and second with the destabilisation device. After 20 min of walking with the destabilisation device, two 30s post-walking trials were collected, first with and second without the destabilisation device. The middle 10 steps of each trial were extracted, plantar pressure quantified, and data averaged across steps for repeated measures ANOVA analysis. Electromyographic data wereextracted from 50 ms pre- through 200 ms post-initial contact. The centre of pressure shifted medially during destabilisation device use (P < 0.002) versus baseline. This shift was notretained upon device removal. Thus, the device capably shifts plantar pressure while worn. Its effects beyond a single sessionare unknown.